Design of an Internet network using HFC networks of San Juan de Lurigancho - Zamudio De León, W. Alejandro (2015)
Presentado en el Congreso Internacional Students Conference on Electrical, Electronics and Computer Science, SCEECS 2016, Bhopal - India, del 05 al 06 de agosto.